Features Associated With Depressive Predominant Polarity and Early Illness Onset in Patients With Bipolar Disorder - García-Jiménez, Jesús; Gutiérrez-Rojas, Luis; Jiménez-Fernández, Sara; González-Domenech, Pablo José; Carretero, María D.; Gurpegui, Manuel (Frontiers in Psychiatry, 2020)
Objective: The aim of this study is to determine the onset polarity (OP), Predominant Polarity (PP) and Onset Age (OA) on a sample of Bipolar Disorder (BD) patients and to determine its association with socio-demographic, clinical and therapeutic variables. Methods: A retrospective and naturalistic study on outpatients diagnosed with BD, were classified according to the OP, PP and OA. In addition, we have collected information about functionality and social support. Multivariate logistic regression analyses were used to identify the variables showing the cross-sectional association with the PP. We defined Manic-PP when a patient suffers more relapses into the manic pole whilst a Depressive-PP is the one who had more depressive episodes. OA was divided into early onset (≤20 years old) and late onset (>20 years old). Results: The sample consisted of 108 BD patients (33M/75F), where 32 had a Manic-PP (29.6%) and 76 a Depressive-PP (70.4%); 32 had a Manic-OP and 76 a Depressive-OP; and 32 had an early onset and finally, 76 had a late onset. In the logistic regression analyses, the hospital admission variables, the high score on CGI scale and Depressive-OP were significantly associated with the Depressive-PP. On the other hand, Depressive-OP was associated with BD type II, great family malfunction, mayor diagnosis delay and depressive-PP. Finally, the early onset of pathology was associated with the delay of diagnosis, more psychotic symptoms, more hospital admissions and greater family dysfunction. Conclusions: The results of this study show that BD patients with Depressive-OP, Depressive-PP or Early onset of the symptomatology could be implied in greater severity, because they are frequently associated with the variables that worsen the prognosis. Our findings match up with the conclusions of two systematic reviews and we also include the concept of family dysfunction that has not been previously analyzed. However, we could not replicate some important associations of previous studies that may be related to the design and methodology used. This work contributes to the use of polarity and the onset age of the BD patients, as it can become a useful instrument in the management of the patient and his surroundings.